Sensitive liquid chromatography-mass spectrometry determination of isoniazid: Elimination of matrix effect - ASSANHOU, Assogba Gabin (My University, 2014)
Small size and high polar basic compounds have always been challenging with heavy matrix effect due to their difficult complete separation from polar endogenous compounds contained in most biological matrix. In this study, a relevant design including column choice, mobile phase constituents, and liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS) parameters optimization have been developed to remove matrix effect and chromatographic peak tail in LC-MS/MS determination of small weight and high polar basic compounds. The designed method was used to establish a rapid, selective and sensitive method for LC-MS/MS determination of Isoniazid (INH). The developed method was validated for the determination of INH in human plasma using a mere protein precipitation for sample preparation and 6-methyl nicotinic acid as internal standard (IS). The chromatographic separation was performed on a Sapphire C18 column under gradient elution program. The mobile phase consisted of methanol and aqueous ammonium acetate buffer at the flow rate of 0.3 ml/min. Electrospray ionization in positive ion mode and selective reaction monitoring were used for the quantification of INH with a monitored transitions m/z 138.1 → 121.0 for INH and m/z 138.0 → 92.1 for the IS. The validated method was linear over the range of 5 to 3000 ng/ml with a lower limit of quantification of 5 ng/ml. The correlation coefficient was r2>0.998. The intra and inter-day precisions of the assay were 1.0 to 4.5 and 2.1 to 11.3%, respectively. In this study, the weak separation issue and matrix effect have been overcome, the chromatographic peak tailing circumvented and method sensitivity improved.
Keywords: Isoniazid; liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS); matrix effect; high polar basic compounds.